Pengaruh Media Bioskop Mini terhadap Kemampuan Mengenal Bentuk Geometri pada Anak Usia 4-5 Tahun di TK Aisyiyah 2 Kecamatan Mandau Duri - Gita Febriyanti; Zulkifli Zulkifli; Enda Puspitasari (Departement of Mathematics Education, 2023)
Geometry ability is an ability that needs to be learned from an early age. Mini cinema games can be one of the simple games designed to help children aged 4-5 years recognize geometric shapes. This study aimed to determine the influence of mini cinema media on the ability to recognize geometric shapes in TK Aisyiyah 2, Mandau Duri District. The research used was experiment conducted with a one group pretest-posttest research design, namely experimental research conducted in one group. The data analysis technique was paired samples t-test using the Statistical Program for Social Science software (SPSS version 25). The results of this study indicated that there is a very significant effect of using mini cinema media on the ability to recognize geometric shapes before and after carrying out the experiment by giving treatment in the form of mini cinema media in children aged 4-5 years at Aisyiyah 2 Kindergarten, Mandau Duri District. The effect is equal to 71.42%, and based on the Normalized Gain assessment criteria, it is in the medium category.